Technical review of radiative-property modeling approaches for gray and nongray radiation, and a recommended optimized WSGGM for CO2/H2O-enriched gases - Osama A. Marzouk (Results in Engineering, 2025)
Thermal radiation through radiatively-active gases is a complex problem due to the spectrally-dependent behavior (i.e., the absorption of electromagnetic radiative energy) of constituent species in gaseous media. Oxy-fuel combustion (OFC) is an example where thermal radiation becomes important due to both the high temperature, and the presence of a high concentration of the radiatively-active gaseous species carbon dioxide (CO2) and water vapor (H2O) during this oxygen-enriched combustion. Precise modeling of the spectral behavior of radiatively-active gases through detailed approaches, such as the line-by-line (LBL) approach or the statistical narrow band (SNB) approach is computationally formidable, and thus simplified techniques are sought as practical alternatives for numerical modeling through computational fluid dynamics (CFD) solvers. In the current study, we consider the weighted-sum-of-gray-gases model (WSGGM) as a desired simplified approach to estimate the radiative properties needed for radiation calculation when numerically simulating oxy-fuel combustion as well as other processes involving high temperatures with high concentrations of CO2 and/or H2O. We examine the ability of seven existing WSGG models to evaluate accurately the total emissivity over the full range of the H2O-to-CO2 molar ratio (from 0 to infinity), and we examine the suitability of these seven WSGGMs for oxy-fuel combustion. We compare the performance of these seven WSGGMs models to a reference solution obtained using the spectral line-based weighted-sum-of-gray-gases (SLW) approach in terms of predicted total emissivities and predicted radiative heat fluxes in a 3D enclosure with different temperatures and chemical compositions when either a gray radiation solution method (solving a single radiative transfer equation, “RTE”) or a nongray radiation solution method (solving multiple radiative transfer equations) is followed. Based on the obtained results, we recommend the comprehensive five-gray-gas WSGGM, and provide the entire list of its 240 parameters. The study also presents results that help contrast several modeling approaches when used for emissivity predictions for a CO2/H2O mixture at different temperatures and pathlengths. These approaches are the LBL approach based on the HITEMP (HIgh-TEMPerature) spectroscopic molecular absorption database, the RADCAL and EM2C implementations of the statistical narrow band (SNB) approach, and the exponential wide band (EWB) approach.